BOOK REVIEW : The Lowland by Jumpa Lahiri - Sefra, Venessa Khairifa (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
Lahiri, Jhumpa. The Lowland. New York: Alfred A. Knopf, 2013, 340 pages